NK Cell Precursors in Human Bone Marrow in Health and Inflammation - Bozzano, Federica; Perrone, Carola; Moretta, Lorenzo; De Maria, Andrea (Frontiers in Immunology, 2019)
NK cells are generated from hematopoietic stem cells (HSC) residing in the bone marrow (BM), similar to other blood cells. Development toward mature NK cells occurs largely outside the BM through travel of CD34+ and other progenitor intermediates toward secondary lymphoid organs. The BM harbors multipotent CD34+ common lymphoid progenitors (CLPs) that generate T, B, NK, and Dendritic Cells and are devoid of erythroid, myeloid, and megakaryocytic potential. Over recent years, there has been a quest for single-lineage progenitors predominantly with the objective of manipulation and intervention in mind, which has led to the identification of unipotent NK cell progenitors devoid of other lymphoid lineage potential. Research efforts for the study of lymphopoiesis have almost exclusively concentrated on healthy donor tissues and on repopulation/transplant models. This has led to the widely accepted assumption that lymphopoiesis during disease states reflects the findings of these models. However, compelling evidences in animal models show that inflammation plays a fundamental role in the regulation of HSC maturation and release in the BM niches through several mechanisms including modulation of the CXCL12-CXCR4 expression. Indeed, recent findings during systemic inflammation in patients provide evidence that a so-far overlooked CLP exists in the BM (Lin−CD34+DNAM-1brightCXCR4+) and that it overwhelmingly exits the BM during systemic inflammation. These “inflammatory” precursors have a developmental trajectory toward surprisingly functional NK and T cells as reviewed here and mirror the steady state maintenance of the NK cell pool by CD34+DNAM-1−CXCR4− precursors. Our understanding of NK cell precursor development may benefit from including a distinct “inflammatory” progenitor modeling of lymphoid precursors, allowing rapid deployment of specialized Lin−CD34+DNAM-1brightCXCR4+ -derived resources from the BM.